Exotic associations and presentations of an age old disease: spectrum of tuberculosis in a developing country - Jetley, Sujata; Jairajpuri, Zeeba S.; Pujani, Mukta; Khan, Sabina (International Journal of Research in Medical Sciences, 2017)
Background:To create an awareness of the associations of tuberculosis with various other infections and its atypical clinical manifestations is important especially in regions where tuberculosis continues to be a major public health problem. Methods: This was an observational study of tubercular cases received in the Department of Pathology during the period January 2014 to January 2015. Results: A case series of exotic associations of tuberculosis, along with two cases at unusual sites, not suspected clinically, subsequently diagnosed by pathological examination and ancillary techniques. Conclusions: Tuberculosis continues to be a major cause of morbidity and mortality especially in the developing world. This series of cases goes to demonstrate the seemingly endless forms and presentations of this age-old disease and the importance of timely diagnosis and specific treatment.